"I Have Seen the Opportunities That Science Brings": Encouraging Girls to Persist in Science. Issue 2 (3rd April 2019) - Skipper, Yvonne; de Carvalho, Eloise
Abstract: Women are underrepresented in science careers. To overcome this, it is important to explore how to encourage girls to continue to study science. This intervention involved girls aged 12–14 attending interactive science sessions at a university. Girls completed questionnaires before and after the session. Through the intervention, girls became more likely to believe they could succeed in science and saw it as both more useful and interesting. However, the timing of this intervention appeared to be too late. Many girls had already decided on a career and stated that they would be unlikely to continue to study science if it was not needed in their chosen career.